If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(4 + a) = 0 (4 * -4 + a * -4) = 0 (-16 + -4a) = 0 Solving -16 + -4a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -4a = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -4a = 0 + 16 -4a = 0 + 16 Combine like terms: 0 + 16 = 16 -4a = 16 Divide each side by '-4'. a = -4 Simplifying a = -4
| m+14=-3 | | 5(3+6x)-2=163 | | (a+2)/(2)=-1 | | 10+6q=14+5q | | 37-6x=61-2x | | -3(6y-7)-y=-3(y-2) | | 5x^9*2u*2u^2x^9= | | 7(7n+3)-10(n-9)= | | 3/10t=6 | | y-13=-4 | | 0=8r-3r | | 2(a+1)=3(a-2)-a | | 3m+6=-6+m | | 10+m/2=6 | | q=-45/-3 | | 2(x+4)-5(x-3)=34 | | 6x-6-8=4x-4+6-2x | | 8+7x=78 | | 5n+7n=-12 | | 6+15y-3=8y+107-6y | | 5(a-12)-24=3(s+2) | | 5x-7-3x=19 | | (8t+30)+(-2-16)=-22 | | (x-5)/(2)=(x+2)/(3) | | (-11)(-15)=y | | 7p-5(3+p)= | | 6.42-10d=25 | | 6x^2+45x=180 | | 2(3t-8)-4t=2 | | -x-12=45 | | 1-8m=-5m+16 | | 8a-4-4a=6-a |